16S rRNA gene amplicon dataset of prokaryotic communities from a subantarctic marine ecosystem: Ushuaia Bay and surrounding waters - Rodriguez Florez, Clara Natalia (2020)
We provide a 16S rRNA gene dataset of prokaryotic assemblages of a subantarctic marine ecosystem. Samples were collected at 2 stations (one near Ushuaia Bay and the other close to Bridges islands in the Beagle Channel). At each station, 2 depths (subsurface and bottom waters) were sampled in february, march, may and september during 2018, giving a total of 10 samples. 16S rRNA gene amplicon sequencing (V4 hypervariable region) was performed with the Illumina MiSeq platform. A total of 1116 amplicon sequence variants (ASVs) were recovered from the dataset. The sequences were taxonomically assigned to Alphaproteobacteria (23 ± 2%, mean ± standard error), Gammaproteobacteria (17 ± 1.5%), Flavobacteriia (8 ± 2%), Deltaproteobacteria (3.7 ± 0.5%), Acidimicrobiia (1.7 ± 0.1%), Planctomycetia (1.9 ± 0.4%), and AB16 group (1.7 ± 0.3%). Sequences affiliated with Archaea were abundant, reaching one third of analyzed sequences, mainly Thaumarchaeota (22 ± 3%), and Thermoplasmata (10 ± 1%). Together, sequences assigned to all these groups accounted for more than 90% of the sequences. This dataset constitutes a valuable resource for future scientific research aiming to unveil the role of these communities in ecosystem services such as carbon and nutrient cycling, and pollutants degradation. This will turn into benefits for future environmental monitoring and preservation actions, considering the tangible heritage of Ushuaia Bay and surrounding waters.